Exploration and Studies of Wild Cymbopogon martinii (Roxb.) Wats. Growing in Devarayana Durga Hill, Karnataka - Murthy, Ashwini; Jagadeeshan, Vidya; KJ, Thara Saraswathi (Asian Journal of Biological and Life Sciences)
Cymbopogon martinii is an aromatic plant commercially grown for its valuable essential oil, which is used in the pharmaceutical and aromatic sectors. Antimicrobial, antifungal, antiviral, anthelmintic, antioxidant, and chemopreventive medicines are all found in the oil. The widespread growth of Cymbopogon martinii was observed in the Devarayana Durga hills of Tumkur, Karnataka, India. The plant was identified using morphological, cytogenetic, and anatomical characteristics (SEM and Microscopic studies). DNA barcoding and flow cytometry analysis was used to confirm ploidy and species specificity. The plant was identified as Cymbopogon martinii (Roxb.) Wats. The seeds and the Herbarium (AC-62/2021) were deposited at the ICAR’s National Bureau of Plant Genetic Resources (NBPGR), Pusa New Delhi. The morphology of the wild plant differed from that of other C. martinii kinds gathered and analyzed from the same wild area, indicating a response to environmental influences. Flow cytometry was used to confirm that the species was tetraploid (C.flexuosus). Using NCBI BLAST, the DNA barcoding sequence of rbcL revealed close similarities to C. martinii, and the sequence was deposited in Gen Bank under the accession number MW538957. As a result, conserving wild C. martinii would aid in the development of new breeding lines with potential bioactive chemicals with an economic worth in the future.
Keywords: Authentication; DNA Barcoding; Exploration; Flow cytometry analysis; Morphological study; Wild Cymbopogon martinii